2019
DOI: 10.1016/j.carbon.2018.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Revealing lattice disorder, oxygen incorporation and pore formation in laser induced two-photon oxidized graphene

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…This is a consequence of the reduced thermal diffusion and more efficient ablation process due to the incidence of laser energy in a restricted volume triggering photochemical processes (multiphoton absorption, direct photodissociation of atomic bonds, etc.) [186][187][188]. The presence of graphene wrinkles increases the ablation probability due to the concomitant reduction of electrical and thermal conductivities leading to increased energy accumulation [189].…”
Section: Treatments Based On Laser Ablationmentioning
confidence: 99%
“…This is a consequence of the reduced thermal diffusion and more efficient ablation process due to the incidence of laser energy in a restricted volume triggering photochemical processes (multiphoton absorption, direct photodissociation of atomic bonds, etc.) [186][187][188]. The presence of graphene wrinkles increases the ablation probability due to the concomitant reduction of electrical and thermal conductivities leading to increased energy accumulation [189].…”
Section: Treatments Based On Laser Ablationmentioning
confidence: 99%
“…[35] Further increase to the exposure causes higher lattice disorder (stage 2), [35] observed as a decrease of A D / A G with simultaneous broadening of the G band. [27,28,36] The creation of active sites to facilitate the nucleation is necessary to perform ALD on a graphene surface. It has been shown that laser-induced 2-PO breaks the sp 2 -bonds in graphene and forms sp 3 -type defects with out-of-plane covalent functional groups.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[24] Previously, our group has demonstrated a femtosecond laser irradiation technique based on a two-photon oxidation (2-PO) process, wherein oxygen containing groups are incorporated into the graphene lattice through exposure to femtosecond laser pulses under ambient atmosphere. [25][26][27] This leads to the formation of hydroxyl and epoxy groups on the graphene surface under moderate laser exposures and carboxyl groups at near-to-ablation exposure levels. [28] This technique allows for tuning the oxidation level of the graphene [28] and for the possibility of preparing arbitrary patterns with high spatial resolution (300 nm).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of disorder or defects in the graphene sheets, such as vacancies, oxygen-containing functional groups and/or adsorbed molecules, is revealed by the presence of D-band, centered close to 1350 cm -1 [41,42]. The bands centered close to 2700 and 2900 cm -1 are known as the secondorder contribution of D-band (named 2D) and the combination of G and D bands (named D + G), respectively [43].…”
Section:  / O 2 / Omentioning
confidence: 99%